2017
DOI: 10.4236/ojpsych.2017.72009
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Learning Styles and Students’ Identity Styles

Abstract: The aim of this study was to investigate the relationship between learning styles and identity styles Students. The study consisted of all high school students and community solidarity (second period) in the 2014-2015 school year resident of the city of Sabzevar that 100 people were selected by multistage random cluster sampling. Kolb's Learning Styles Inventory Tool questionnaire identity styles Bennion-Adams used the results showed that successful identity styles between style concrete experience, reflective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 9 publications
(11 reference statements)
1
12
0
2
Order By: Relevance
“…Also, according to the time to think before acting and to assimilate before commenting or demonstrating the concepts to appreciate their personality. These finding supports Alavi and Toozandehjani [24], that most people have a preference to identifiable method of interacting with, taking in, and processing information. Besides, the study agrees with the findings of Kaushik [25] in his study that attempts to bridge David Kolb's theory of Learning Styles with Gardner's Theory of Multiple Intelligences to overcome criticisms to both that different learner have a preferred way of thinking, processing, and understanding information.…”
Section: Preferred By Way Of Processing Information In Learningsupporting
confidence: 80%
See 1 more Smart Citation
“…Also, according to the time to think before acting and to assimilate before commenting or demonstrating the concepts to appreciate their personality. These finding supports Alavi and Toozandehjani [24], that most people have a preference to identifiable method of interacting with, taking in, and processing information. Besides, the study agrees with the findings of Kaushik [25] in his study that attempts to bridge David Kolb's theory of Learning Styles with Gardner's Theory of Multiple Intelligences to overcome criticisms to both that different learner have a preferred way of thinking, processing, and understanding information.…”
Section: Preferred By Way Of Processing Information In Learningsupporting
confidence: 80%
“…The findings of this study demonstrates and supports Wouter and Katrien [29] that assessment of concept learning styles needed a more appropriate articulation of the discourse to help reduce misunderstandings in the preference of learning styles. Past research work held that the assumption that people can be clustered in different groups is not supported by empirical evidence [24,29]. The clustering contributed to the misunderstandings.…”
Section: Resultsmentioning
confidence: 99%
“…Knowledge of the various learning style preferences of students admitted in Science Education programme will eventually lead to more effective learning experiences. Alavi and Toozandehjani (2017) revealed that learning styles of students can enhance their learning. In the same vein, Barman et al (2014) study on learning style and academic performance of students conclude that students' knowledge of their learning style can improve their academic performance.…”
Section: Author(s) Agree That This Article Remain Permanently Open Acmentioning
confidence: 99%
“…Just as the learners learn in different ways, so also teachers teach in different ways. In fact, Alavi and Toozandehjani (2017) concluded that having a background of the learning styles of students can enhance their learning and at the same time help students strengthen self-actualization. Teevan, Michael and Schlesselman (2011) also emphasize that knowledge of the learning styles can help facilitate teachers to employ suitable teaching strategies and methods to nurture students' academic performance.…”
Section: Introductionmentioning
confidence: 99%